2015
DOI: 10.1002/hbm.22762
|View full text |Cite
|
Sign up to set email alerts
|

Development of effective connectivity in the core network for face perception

Abstract: This study measured effective connectivity within the core face network in young children using a paediatric magnetoencephalograph (MEG). Dynamic casual modeling (DCM) of brain responses was performed in a group of adults (N = 14) and a group of young children aged from 3 to 6 years (N = 15). Three candidate DCM models were tested, and the fits of the MEG data to the three models were compared at both individual and group levels. The results show that the connectivity structure of the core face network differs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 99 publications
(176 reference statements)
1
7
0
Order By: Relevance
“…Furthermore, that the reading‐related ventral activations have the same topography in blind and sighted subjects suggests that connections with language may be critical and may serve as powerful constraints in determining the standard location of the VWFA even in the absence of visual input. Lastly, recent findings of more effective interhemispheric connectivity between the posterior cortex in children aged (mean) 4.5 years than in adults is also consistent with the hypothesis that there are changes in network properties that occur over development around the time that children are entering school and being exposed to orthography …”
Section: Predictions and Further Evidencesupporting
confidence: 75%
“…Furthermore, that the reading‐related ventral activations have the same topography in blind and sighted subjects suggests that connections with language may be critical and may serve as powerful constraints in determining the standard location of the VWFA even in the absence of visual input. Lastly, recent findings of more effective interhemispheric connectivity between the posterior cortex in children aged (mean) 4.5 years than in adults is also consistent with the hypothesis that there are changes in network properties that occur over development around the time that children are entering school and being exposed to orthography …”
Section: Predictions and Further Evidencesupporting
confidence: 75%
“…Regarding with the intra-area connection, the occipital visual cortex is believed to be part of the core face network and important for face feature detection (Pitcher et al, 2011 ; Arcurio et al, 2012 ; Joseph et al, 2012 ). Previous studies also found that the OFA/FFA connectivity in the occipital area increased with age (He et al, 2015 ; Song et al, 2015 ). Thus, although fNIRS is unable to reach the depth of OFA/FFA, the increased connectivity inside the occipital area indicated that children become more sensitive to the face features with increased age.…”
Section: Discussionmentioning
confidence: 68%
“…Specifically, children at both ages exhibited weaker connectivity between the inferior occipital gyrus (IOG) and the FG, and no significant connectivity between the IOG and STS (see Figure (a)). Findings in even younger children between 3 and 6 years of age have also alluded to the presence of additional connectivity between the OFA and the contralateral FFA—connections that are likely eliminated alongside a reorganization of brain function during development …”
Section: Developing An Expertise For Processing Facesmentioning
confidence: 99%